2018
DOI: 10.1002/net.21804
|View full text |Cite
|
Sign up to set email alerts
|

Optimal wind farm cable routing: Modeling branches and offshore transformer modules

Abstract: Many EU countries aim at reducing fossil fuels in the near future, hence an efficient production of green energy is very important to reach this goal. In this article, we address the optimization of cable connections between turbines in an offshore wind park. Different versions of the problem have been studied in the recent literature. As turbines are becoming still more customized, it is important to be able to evaluate the impact of new technologies with a flexible optimization tool for scenario evaluation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
29
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 20 publications
0
29
0
3
Order By: Relevance
“…Especially for offshore wind farms, 20% of total installation cost is resulted from cable and cable installation cost. Total cable cost is proportional with the length of total cables installed among turbines and transmitter [6][7][8][9][10]. The cable cost can be decreased in overall up to 10% by optimizing the cable layout problem [11].…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Especially for offshore wind farms, 20% of total installation cost is resulted from cable and cable installation cost. Total cable cost is proportional with the length of total cables installed among turbines and transmitter [6][7][8][9][10]. The cable cost can be decreased in overall up to 10% by optimizing the cable layout problem [11].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Selection and determination of the wind farm site, determination of turbine locations (TL) on the wind farm, designing electrical infrastructure and cable layout (CL) are the main design problems in the installation of an offshore wind farm [2,3,5,9,10,11]. TL and CL problems, in the literature, are solved in sequentially due to the difficulties in solving both the problems.…”
Section: Introductionmentioning
confidence: 99%
“…A cyclic cable layout, also referred to as a closed-loop structure (Fischetti and Pisinger 2018b), entails higher construction costs of the wind farm, but can compensate financially in terms of improved reliability. In the case of a cable failure, the repair process may be time consuming because specialized vessels and crew have to be available and the maintenance operations require favourable weather conditions.…”
Section: Introductionmentioning
confidence: 99%
“…They conducted experiments on a testbed of real‐world cases and showed that the matheuristics are able to find cost‐effective cable layouts. Fischetti and Pisinger also solved the same cable connection problem in Fischetti and Pisinger using mixed integer models. Banzo and Ramos developed a MIP to determine the cable layout by including system efficiency, investment costs, and system reliability for a real offshore wind farm.…”
Section: Introductionmentioning
confidence: 99%